Employees’ Participation in Organizational Environmental Management: A Case Study of Unison Laboratories Co.Ltd. - คำเบ้า ประภาพร; อึ้งสิทธิพูนพร วรรณี; สุปัญโญ วีรฉัตร (Journal of Behavioral Science for Development, 2014)
การมีส่วนร่วมของพนักงานในการจัดการสิ่งแวดล้อมภายในองค์กร: กรณีศึกษา บริษัท ยูนีซัน จำกัด This research was aimed to 1) investigate employees’ participation in organizational environmental management, 2) compare employees’ participation in organizational environmental management, and 3) explore employees’ suggestions toward the increase of an effectiveness in promoting employees’ participation in organizational environmental management. Unison Laboratories Ltd. was selected as a case study. 225 research sample comprised 192 operational level employees and 33 executives obtained by stratified sampling technique. Research instrument was a survey questionnaire. Statistics for data analysis were mean, and standard deviation. The research findings were as follows. 1) The overall sample participated in organizational environmental management at a moderated level ( = 2.61). Activity that got highest average score of participation was the Energy Saving Project ( = 2.72), whereas that got the lowest scores was the 5 S Project ( = 2.46). The participation of sample was mostly in terms of implementation ( = 3.00) while the least was in terms of planning ( = 1.98). 2) There were differences in organizational environmental management participation among sample with different sexes, educational levels, membership of environmental management group, and awareness in environmental management at statistical significant level of .05 3) It was suggested by the sample that participation of employees at all levels could be enhanced through knowledge and understanding provision, participation awareness raising campaigns, information transmission, motivation promotion, and the allocation of adequate time and personnel for organizing the projects on environmental management. Keywords: Participation, Organizational Environmental Management บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาการมีส่วนร่วมของพนักงานในกิจกรรมการจัดการสิ่งแวดล้อมภายในองค์กร 2) เปรียบเทียบมีส่วนร่วมของพนักงานในกิจกรรมการจัดการสิ่งแวดล้อมภายในองค์กร และ 3) เพื่อศึกษาข้อเสนอแนะของพนักงานเกี่ยวกับการส่งเสริมการมีส่วนร่วมในการจัดการสิ่งแวดล้อมภายในองค์กร โดยใช้บริษัท ยูนีซัน จำกัด เป็นกรณีศึกษา กลุ่มตัวอย่างที่ใช้ในการวิจัยมีจำนวนทั้งหมด 225 คน จำแนกเป็นระดับปฏิบัติการจำนวน 192 คน และระดับบริหารจำนวน 33 คน ได้มาด้วยวิธีการสุ่มตัวอย่างแบบแบ่งชั้น เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล ได้แก่ แบบสอบถาม วิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1) กลุ่มตัวอย่างโดยรวมมีส่วนร่วมในกิจกรรมต่าง ๆ เกี่ยวกับการจัดการสิ่งแวดล้อมภายในองค์กร ในระดับปานกลาง (=2.61) โดยกิจกรรมที่มีค่าเฉลี่ยการมีส่วนร่วมมากที่สุด คือ โครงการอนุรักษ์พลังงาน ( = 2.72) กิจกรรมที่มีค่าเฉลี่ยการมีส่วนร่วมน้อยที่สุด คือ โครงการ 5 ส ( = 2.46) เมื่อพิจารณาด้านที่มีส่วนร่วมในการจัดการสิ่งแวดล้อมภายในบริษัท ยูนีซัน จำกัด กลุ่มตัวอย่างส่วนใหญ่การมีค่าเฉลี่ยการส่วนร่วมในการปฏิบัติมากที่สุด ( = 3.00) ด้านที่กลุ่มตัวอย่างส่วนใหญ่มีค่าเฉลี่ยการส่วนร่วมน้อยที่สุด คือ การมีส่วนร่วมในการวางแผน ( = 1.98) 2) กลุ่มตัวอย่างที่มีเพศ ระดับการศึกษา การเป็นสมาชิกกลุ่มกิจกรรมการจัดการสิ่งแวดล้อม และความตระหนักเกี่ยวกับการจัดการสิ่งแวดล้อม ต่างกันมีส่วนร่วมในการจัดการสิ่งแวดล้อมภายในบริษัท ยูนีซัน จำกัด แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3) ข้อเสนอแนะเกี่ยวกับการส่งเสริมการมีส่วนร่วมของพนักงานทุกระดับในการจัดการสิ่งแวดล้อมภายในองค์กร ประกอบด้วยการให้ความรู้ ความเข้าใจ การกระตุ้นจิตสำนึกและความตระหนักในการมีส่วนร่วม การประชาสัมพันธ์ การสร้างแรงจูงใจ ตลอดจนการจัดเวลาและบุคลากรให้เพียงพอสำหรับการจัดกิจกรรมโครงการด้านการจัดการสิ่งแวดล้อม คำสำคัญ: การมีส่วนร่วม, การจัดการสิ่งแวดล้อมภายในองค์กร